Prevalence and correlates of post-traumatic stress disorder and its symptomatology in tornado-affected rural residents - Wu, Tai-Min; Yang, Qin; Huang, Yu-Jie; Zhong, Bao-Liang; Zhang, Juan; Liu, Lian-Zhong (Frontiers in Psychiatry, 2022)
Experiencing a serious natural disaster may place survivors at particularly high risk for posttraumatic stress disorder (PTSD); however, very limited data are available on the prevalence and clinical characteristics of PTSD among survivors of a tornado disaster. The present study examined the prevalence of PTSD and correlates and clinical symptoms of possible PTSD in survivors 1.5 months after a tornado disaster. A total of 237 survivors were recruited and administered the Structured Clinical Interview for DSM-V (SCID) to measure the prevalence of PTSD and the Essen Trauma Inventory (ETI) to measure the incidence of symptoms in each dimension. Survivors’demographic information and characteristics of exposure to the tornado were collected via self-report questionnaires. Thirty-two of the survey respondents were diagnosed with PTSD (13.6%, total=237). Correlates of PTSD in survivors were being female (OR=3.62, P=0.023), living in an area severely affected by the tornado (OR=3.94, P=0.032), and having severe property damage (OR=3.72, P=0.010). Less common symptoms mainly focused on the avoidance dimension and included feeling alienated or distant from the people around oneself (21.90%), not being able to recall important parts of the event (28.10%), being emotionally numb (31.20%), and feeling like one’s plans for the future and hopes will not come true (37.50%). In the sample of rural residents, nearly two-thirds of people with PTSD were not willing to seek psychological help; increasing the accessibility of mental health services and administering more active mental health services are necessary for this vulnerable population, whether or not they claim to need help.